Effects of Different Plastic Mulching Film on Soil Hydrothermal Status and Water Utilization by Spring Maize in Northwest China - Liu, Ruhua; Wang, Zhenhua; Ye, Hanchun; Li, Wenhao; Zong, Rui; Tian, Xulang (Frontiers in Materials, 2021)
The problem of residual film pollution in farmland caused by polyethylene mulching films is serious. The application effects of different mulching films combined with drip irrigation on maize planting in Ili area, Xinjiang, China, were explored. In this study, four types of mulching films and non-mulching treatment were used to study the degradation properties of different plastic mulching and their effects on the dynamic changes of soil moisture, heat and crop yields of maize under drip irrigation. The results showed that after 160 days of mulching film, only small cracks appeared in polyethylene mulching films. The degradation performance of white oxo-biodegradable film treatment was optimal than the black oxo-biodegradable film treatment. The quality loss rate of two biodegradable films were 52.26% and 48.48%, respectively. Various mulching film treatments could both increase soil moisture in the early stage of maize growth. At the 0~60 cm soil layer, the soil moisture under the white oxo-biodegradable mulching film and black oxo-biodegradable mulching film treatments were lower by 2.75% and 2.66% (P < 0.05) than the white polyethylene mulching film and black polyethylene mulching film treatments. The soil water consumption was highest in the non-mulching treatment, followed by biodegradable film, and the small least value was observed in the polyethylene film treatment. The average soil temperature at depth of 0~15 cm in white polyethylene film, black polyethylene film, white oxo-biodegradable film and black oxo-biodegradable film treatments were 1.43℃, 1.16℃, 0.72℃ and 0.64℃ higher than the non-mulching treatment respectively. Mulching films treatment played a critical role in increasing production and improving water use efficiency. The black polyethylene film treatment had the highest yield and the best water use efficiency. The black oxo-biodegradable film treatment only reduces the yield by 0.33% compared with the black polyethylene film treatment, and the water use efficiency was only reduced by 0.90% (P > 0.05). Comprehensive analysis showed that Black oxo-biodegradable film could be used as a substitute for polyethylene mulching film and be applied to the production practice of drip irrigation maize in Ili area.